LOW-TEMPERATURE SUSCEPTIBILITY AND HYSTERESIS OF MAGNETITE - Muxworthy A.R. (My University, 1999)
Measurement of susceptibility (χ) and hysteresis loops below room temperature for large multidomain hydrothermal magnetite and an acicular single domain magnetite are reported. Hydrothermal samples all display frequency dependent anomalies in χ across the Verwey transition (Tv). A second frequency dependent anomaly in χ is found at 50 K. In both cases the frequency dependency of χ is attributed to discontinuities in the hopping frequency of electrons at Tv and 50 K respectively. The coercive force (Hc) of the hydrothermal samples displays sharp discontinuous behavior at the magnetocrystalline anisotropy isotropic point (Tk). On plotting the hysteresis parameters on `Day' plots, the hydrothermal grains move towards more pseudo-single domain-like regions on cooling through Tk. It is suggested that the difference in low-temperature anomalous behavior between `high-field' parameters, e.g., Hc at Tk, and `low-field' parameters, e.g., χ at Tv, is due to the partial destruction of the Vonsovskiǐ exchange interaction in the presence of high-fields, where according the magneto-electronic model of the Verwey transition, the Vonsovskiǐ exchange interaction is the mechanism by which electronic ordering occurs at Tv. The acicular single domain sample displays no anomalous behavior in either χ or hysteresis parameters near Tk or Tv.